Catholicsm's democratic dilemma varieties of public religion in the Philippines - Buckley, David T. (Philippine studies : historical and ethnographic viewpoints, 2014)
"As representatives of public religion in a postauthoritarian setting, Catholic elites face a democratic dilemma and identifies their impacts on the internal life of the church and on alliances between the church and other social actors. These dynamics are illustrated with an analysis of the reproductive health debate and its fallout in the 2013 elections."